2014
DOI: 10.1007/s10461-014-0836-6
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Ball: Implications for HIV Risk and Prevention Among the Constructed Families of African American Men Who Have Sex with Men

Abstract: African American men who have sex with men (AAMSM) are disproportionately burdened by new and existing HIV infections. In spite of this, few HIV prevention interventions have been developed that meet the specific needs of AAMSM and that are culturally appropriate and build on strengths and resources. In this paper, we examine constructed families, including those who belong to houses and those who do not, from a three city sample of 196 AAMSM. Results show that the majority of AAMSM who belong to constructed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…In addition to families that emerge within ballroom houses, independent gay families provide the same kind of familial support and relational structure as ballroom houses but without the added pressures of competition. In that their support is not contingent on winning competitions, it has been posited that independent gay families may be more stable sources of guidance (Dickson-Gomez et al, 2014; Horne et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…In addition to families that emerge within ballroom houses, independent gay families provide the same kind of familial support and relational structure as ballroom houses but without the added pressures of competition. In that their support is not contingent on winning competitions, it has been posited that independent gay families may be more stable sources of guidance (Dickson-Gomez et al, 2014; Horne et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Dickson-Gomez and colleagues (2014) conducted a qualitative study on constructed families among BMSM and found that many BMSM formed alternative family relationships with friends or in “houses” due to the biological families’ rejection of their sexual behaviour and/or identity. According to the key informants, many of these social rejections were often intertwined with homelessness, lack of educational attainment and mental health problems.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of support and availability of role models and experiences of marginalization from their own home communities, many GBT youth search for environments and/or relationships in which they are more freely able to explore their sexual identity development (Bruce, Harper, & ATN, 2011). Again, many Black GBT youth may not feel welcomed in the predominantly White gay community due to racial stigma and therefore form “constructed families” in which unrelated friends assume roles similar to biological families, such that there are parents and siblings sharing common identities, values, and norms (Horne, Levitt, Sweeney et al, 2014; Dickson-Gomez, Owsczarzak, St. Lawrence et al 2014; Bruce, Harper, & ATN, 2011). These constructed families may consist of older gay men assuming the role of mentoring younger gay men or of more extensive gay family networks (Bruce, Harper & ATN, 2011; Horne et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The House Ball Community (HBC) is a nationwide network of underground communities of African American MSM and TG youth who join ‘houses’, family-like structures that are parallel to but distinct from constructed ‘gay families’ of choice (Dickson-Gomez, et al, 2014), and organise elaborate balls (judged competitions between houses in which participants are awarded prizes for displaying mastery of particular performative categories). Members of the HBC are disproportionately impacted by HIV, with prevalence at 17% and 27% in New York and the San Francisco Bay Area, respectively (Arnold and Bailey, in press; Murrill et al, 2008).…”
Section: Introductionmentioning
confidence: 99%